FAKTOR RISIKO PENYEBAB MENINGKATNYA KEJADIAN STROKE PADA USIA REMAJA DAN USIA PRODUKTIF - Noviyanti, Retno Dewi (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Adolescence are the largest population in the world and especially in Indonesia. Adolescence are the future generation, who needs care in all things , especially the quality of healthcare. At the first, stroke is a disease that often affects older people, especially those 50 years old and older, but now stroke can be danger for adolescence and productive age. This occurs because of changes in lifestyle and behaviors, such as eating fast food that contain high levels of fat , smoking , alcohol , overwork , less of exercise and stress, all of these are risk factors of stroke in adolescence and productive age . In addition to the other risk factors are a history of hypertension , systolic blood pressure â¥ 140 and a history of stroke in the family. Especially for adolescence and productive age to maintain a healthy lifestyle and controlling risk factors of stroke at the age so that optimal health can be realized . Keywords: Risk factors, stroke, adolescence and productive age